Strategies for Implementing the Smart Discipline System in Developing Student Morality in Aqidah Akhlak Subjects at MI Al-Hidayah, Prawoto Village, Sukolilo Pati - Anis, Moh Badiul; Qoyyimah, Maria Nurul; Hidayati, Zinatun Nuril (GHAITSA : Islamic Education Journal, 2020)
The purpose of this study was to determine (1) The implementation of the strategy for implementing the smart discipline system in developing the morality of students in the subject of aqidah akhlak in MI. Al-Hidayah Desa Prawoto Sukolilo Pati (2) Supporting and inhibiting factors in implementing the smart discipline system in developing student morality in the subject of aqidah morals in MI. Al-Hidayah, Prawoto Village, Sukolilo Pati. This research method uses a type of field research (field research) and the research approach is a qualitative approach. As for the research location in MI. Al-Hidayah, Prawoto Village, Sukolilo Pati. Furthermore, for data collection the author uses the method of observation, interviews and documentation. The results of this study are known (1) The application of this smart discipline system provides a good contribution to the morality of these students. It is proven that students become more disciplined, have good manners, have respect, are honest, responsible, obey and obey the teacher (2). implementation of the smart discipline system in developing student morality in the subject of aqidah akhlak, there are several supporting factors, namely receiving support from various parties, the enthusiasm of students, the existence of examples from teachers. While the inhibiting factors are differences in the character of students, environmental factors of students who are not good, students do not understand and do not think that the smart discipline system is important for directing children to have good behavior, and students' lack of awareness of the importance of having good morals. good and the consequences for doing deviant actions.